The importance of humanized dental care in public health: Integrative literature review (Research, Society and Development, 2024)
The need for humanized dental care is frequently discussed among dental professionals and health managers, as a more humanistic and interpersonal vision is seen as essential in care routines. Objective: This study aims to highlight the importance of humanized care in dentistry through an integrative literature review. Methodologies: This is an integrative literature review, using the SciElo, PubMed and BVS databases. The descriptors "care And dentistry And humanization" were used to carry out the research, which led to 55 studies from these databases. After screening, 14 studies were selected for this research. It can be seen that in routine clinical dentistry; situations repeatedly arise in which there is anxiety and fear of dental procedures. In this sense, practices such as effective communication and respect for the patient's individuality are strategies that reduce feelings of fear and anxiety, demystifying possible negative experiences and promoting patient health with the empathy needed to achieve the expected prospects.